Effects of irradiation on bone invasion of breast cancer cells - Srimawong, Preeyaporn; Sawajiri, Masahiko; Terato, Hiroaki; Maruyama, Kouichi; Tanimoto, Keiji (Journal of Thai Association of Radiation Oncology, 2017)
Background: Periostin is overexpressed in metastases from bone cancer. Many studies have indicated that periostin plays an important role in bone metastasis. Radiotherapy improves local tumor control, but recent evidence suggests that irradiation of the target tumor can promote tumor invasion and metastasis. Objective: The purpose of the study was to examine the effects of irradiation with carbon ion or gamma ray on the expression of periostin in breast cancer cells and the cytokine levels of osteoblasts in bone tumor metastases. Materials and methods: Breast cancer cells (FM3A/R cells) were exposed to carbon ion or gamma ray and then cocultured with non-irradiated osteoblastic MC3T3-E1 cells. Periostin expression in breast cancer cells and the levels of cytokines influencing bone invasion in osteoblastic cells were measured. Results: Periostin expression increased after irradiation with carbon ion or gamma ray. Carbon ion-irradiated cells expressed less periostin than did gamma ray-irradiated cells. Carbon ion irradiation stimulated low levels of periostin synthesis than gamma ray irradiation. The cytokines influencing bone invasion levels rose in tandem with the increase in periostin level. Conclusions: Carbon ion irradiation may reduce the production of bone-destroying cytokines and vascularization factors by osteoblasts in the microenvironment of cancer invasion in bone. A combination of carbon ion irradiation and a periostin inhibitor would improve treatment of bone metastatic breast cancer.